The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2427.2005.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and temperature effects on planktonic rotifers and crustaceans in northern temperate lakes

Abstract: 1. Anthropogenic stressors such as climate change, ozone depletion and acidification may act in concert to alter ultraviolet (UV) light and temperature regimes in freshwater ecosystems. These physical and chemical changes will inevitably affect zooplankton community dynamics, but little is known about their relative effects on different species in natural communities. During spring, species that migrate to surface waters to take advantage of warmer temperatures may be especially vulnerable as UV levels can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 42 publications
2
28
2
1
Order By: Relevance
“…This finding agreed with the reported suppression of copepods under warmed, fishless conditions (McKee et al 2002). Further, combined exposure to UV and cold temperatures can be advantageous for copepods, such as Leptodiaptomus minutus, that can rely on photoprotective pigmentation (Leech and Williamson 2000;Persaud and Williamson 2005).…”
Section: Discussionsupporting
confidence: 82%
“…This finding agreed with the reported suppression of copepods under warmed, fishless conditions (McKee et al 2002). Further, combined exposure to UV and cold temperatures can be advantageous for copepods, such as Leptodiaptomus minutus, that can rely on photoprotective pigmentation (Leech and Williamson 2000;Persaud and Williamson 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Grazing may increase UV transparency through decreasing the density and altering the size structure of phytoplankton or decreasing the release of dissolved organic matter (DOM) by phytoplankton; thus, zooplankton can contribute to the development of a UV clear-water phase (Williamson et al 2007). UVR can also affect survival and fecundity of zooplankton (Leech and Williamson 2000;Grad et al 2003;Persaud and Williamson 2005), as well as alter abundance of food resources or predators (''solar cascade hypothesis ''-Williamson 1995;Williamson et al 1999).…”
Section: Effect Of Ultraviolet Radiationmentioning
confidence: 99%
“…Zooplankton survival and reproduction can be severely reduced at UVR levels found in the surface waters of highly-transparent lakes; however, effects are species-specific and may depend on other environmental factors such as temperature (Leech & Williamson, 2000;Williamson et al, 2002;Persaud & Williamson, 2005). In a laboratory experiment with monochromatic light, Storz & Paul (1998) found that Daphnia magna were positively phototactic to light from the visible spectrum but negatively phototactic to UVR.…”
Section: Introductionmentioning
confidence: 95%